Morava na úsvitě dějin - Merinsky, Zdenek (Brno : Muzejní a vlastivědná společnost, 2011)
Zusammenfassung.
Bibliografija: str. 622-651
Keywords: Moravska; Velika Moravska; povijest srednjeg vijeka; arheološka nalazišta; seoba naroda; Slaveni; Mikulčice